2018
DOI: 10.1016/j.mce.2017.11.013
|View full text |Cite
|
Sign up to set email alerts
|

Reverse T3 interacts with αvβ3 integrin receptor and restores enzyme activities in the hippocampus of hypothyroid developing rats: Insight on signaling mechanisms

Abstract: In the present study we provide evidence that 3,3',5'-triiodothyronine (reverse T, rT) restores neurochemical parameters induced by congenital hypothyroidism in rat hippocampus. Congenital hypothyroidism was induced by adding 0.05% propylthiouracil in the drinking water from gestation day 8 and continually up to lactation day 15. In the in vivo rT exposure, hypothyroid 12-day old pups were daily injected with rT (50 ng/kg body weight) or saline until day 14. In the ex vivo rT treatment, hippocampal slices from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 83 publications
0
5
0
Order By: Relevance
“…While it is unclear from the data here if this is causative to the observed radial glia phenotype, others have shown that loss of neuroepithelial adherens junctions induce changes in radial glia structure and function, which can lead to cortical heterotopia 17,31,38,39 . With regards to thyroid signaling, differential expression of adherens junctions components like actin filaments and integrins have been reported in the brains of developing hypothyroid rodents 33,4043 , and several other studies have shown that both T4 and reverse T3 (rT3) can directly modify cytoskeletal components via extranuclear signaling pathways 40,4446 . Therefore dysregulation of TH signaling, even for a finite developmental period, may convergently affect cell junctions within the brain.…”
Section: Discussionmentioning
confidence: 99%
“…While it is unclear from the data here if this is causative to the observed radial glia phenotype, others have shown that loss of neuroepithelial adherens junctions induce changes in radial glia structure and function, which can lead to cortical heterotopia 17,31,38,39 . With regards to thyroid signaling, differential expression of adherens junctions components like actin filaments and integrins have been reported in the brains of developing hypothyroid rodents 33,4043 , and several other studies have shown that both T4 and reverse T3 (rT3) can directly modify cytoskeletal components via extranuclear signaling pathways 40,4446 . Therefore dysregulation of TH signaling, even for a finite developmental period, may convergently affect cell junctions within the brain.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, TH modifications, including decarboxylation, deamination, ether-link cleavage, sulfation, and glucuronidation, affect their bioactivity and downstream metabolism (Figure 1). Most of them lead to deactivation and eventually degradation of THs (26), however some of the generated compounds, such as rT3 (44, 45), iodothyroacetic acids (tetrac and triac) and thyronamines (4650), have been shown to convey biological effects in specific contexts. The conversions and main metabolites of THs are shown in Figure 1.…”
Section: Production and Metabolism Of Ths—maternal And Fetal Sourcesmentioning
confidence: 99%
“…It is also speculated that rT3 has direct effects on mortality, but not yet completely clarified. In experimental animal studies, it was shown that rT3 might interact with the integrin avB3 reducing the oxidative stress induced by congenital hypothyroidism in the hippocampus of immature rats, 42 whereas rT3, through non-genomic mechanisms, can increase calcium uptake in Sertoli cells of immature rats 43 and participate in the regulation of actin polymerization of neurons of the central nervous system. 44 Besides, in addition to direct actions, rT3 may act as a competitive inhibitor disrupting T3 signaling that may correlate with unfavorable prognosis.…”
Section: Discussionmentioning
confidence: 99%